Everywhere Regularity for Weak Solutions to Variational Inequalities of Triangular Form (Journal of Partial Differential Equations, 1992)
In this paper, we obtain two results of weak solutions to variational inequalities of triangular form under controllable growth and a class of natural growth conditions, i.e. 1^&#176. L^p-estimate for the gradient; 2^&#176. C^{1,&#946}_{loc}(&#937, R^N) regularity.